Moderasi Beragama dalam Kearifan Lokal Toraja: Misa’ Kada Dipotuo, Pantan Kada Dipomate - Anthonius Michael; Lusia Nopita Pongtiangin; Cornelius Arnoltus (CV. Multi Kreasi Media, 2022)
Indonesia is a multicultural country because which consist of various ethnic groups, cultures, religions, and races. Nevertheless, Indonesia has a motto to unite these differences, namely